Determinants of 30-day Morbidity in Adult Cranioplasty: An ACS-NSQIP Analysis of 697 Cases. Issue 12 (December 2019) - Armstrong, Rachel E.; Ellis, Marco F.
Abstract : Background: Cranioplasty is performed to restore the function and anatomy of the skull. Many techniques are used, including replacement of the bone flap and reconstruction with autologous or synthetic materials. This study describes the complication profile of adult cranioplasty using a prospective national sample and identifies risk factors for 30-day morbidity. Methods: The American College of Surgeon's National Surgery Quality Improvement Project database for 2015–2016 was utilized. Cases were identified by current procedural terminology code, size, and type (autologous/alloplastic). χ2, Fisher exact, and ANOVA tests compared demographic differences. Univariate and multivariate logistic regressions were performed to identify risk factors for 30-day morbidity and mortality. Results: Six hundred ninety-seven cranioplasty cases were identified. Two cases used 2 types of cranioplasties and were counted in both groups. Five hundred forty-three cranioplasties were alloplastic, 57 were autologous, and 99 were classified as "Other." Age, race, diabetes, ventilator dependency, congestive heart failure, hypertension, wound infection, sepsis, and bleeding disorders were identified on univariate analysis to increase complication risk. Multivariate analysis identified age of the patient, systemic sepsis, and bleeding disorders as significant risk factors for complications. There was no difference in complications between cranioplasty types. Overall and medical complications were greater in cranioplasties >5 cm ( P < 0.001). Conclusions: Cranioplasty is a morbid procedure, with a complication rate of 27.4% and a mortality rate of 3.0% in this national sample. Factors such as age, sepsis, bleeding disorders, and size increase risk. Identification and modification of risk factors may guide operative timing and influence informed consent. Abstract : Supplemental Digital Content is available in the text.